Antecedents of Millennial Generation Consumptive Behavior: The Role of Financial Literacy as a Moderation - Suprayitno, Eddi; Tarigan, Nur M Ridha; Purba, Anwar Soleh (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: In order to create a model of the Millennial Generation's Consumptive Behavior Antecedents, this study will investigate the aspects that impact students' consumption behavior: The Moderating Function of Financial Literacy.Methodology: This study is fundamental in nature. Since 150 questionnaires were sent, it is anticipated that at least 30 students will return the questionnaire. Partial Least Square (PLS) using Smart PLS 3.0 software, or a variance-based structural equation test, is the analysis technique employed.Finding: Consumer behavior was not partially influenced by lifestyle, self-concept, or peer group, according to the study's findings. There was no moderating effect of financial literacy on the relationship between lifestyle and consumer behavior. Self-concept's influence on consumer behavior was not moderated by financial literacy. There was an impact of financial literacy on students' consumer behavior, and it did not mitigate the influence of peer groups on consumer behavior.Conclusion: This study found that the factors causing consumer behavior in students consist of internal factors including motivational factors and external factors including lifestyle factors, role models or reference groups, self-identification model factors, and family factors.